A triangulação Libras-português-inglês: relatos de professores e intérpretes de Libras sobre aulas inclusivas de língua estrangeira. - Moraes, Antonio Henrique Coutelo de (2018)
The theme of teaching a foreign language to deaf people has been gaining ground in the Academy's research in the last decades, with a view to "breaking crystals", that is, undoing crystallized beliefs about this process. The results found in the master's degree, as well as those found in the readings, pointed out some relation between the three languages involved in the English classroom frequented by deaf students. From this point of view, interest in the PhD research was developed with the objective of analyzing the effect of pedagogical practices and interactions in English language classes mediated by Libras / Portuguese, in Elementary and Middle School, based on the reports of interpreters and teachers – bilingual or not. The work was developed from a bilingual perspective. We understand bilingualism as referring to the repertoire of languages that many individuals can use, thus involving the first language (L1), the second (L2) and the third (L3), which is foreign (FL) – in the case of this thesis, the languages are, respectively, Libras, Portuguese and English. In order to reach our objective, we seek to base ourselves on Grosjean, Moraes, Pagura, Paiva, Sousa, Vygotsky, among others. The methodology used was the qualitative of a descriptive character in order to better describe, understand and explain the characteristics of the English classroom dynamics. According to Triviños' guidelines, the triangulation of data suggested by the author can be identified when we used the analysis of documents that guide the pedagogical work with the deaf, semi-structured interviews, and the observation of actions and interactions of the research subjects. Data were analyzed using Bardin’s content analysis. The results point to the fact that little English is taught to all students – deaf or hearing – and that the deaf seem to be even more marginalized in the foreign language classroom. We expect, with this thesis, to contribute to the discussions about the quality of the teaching of FL for deaf people, mobilizing teachers to broaden their theoretical and methodological proposals vis-a-vis that language.